PEMBINAAN KEPALA DESA TERHADAP POSYANDU DI DESA BARU KECAMATAN SIAK HULU KABUPATEN KAMPAR TAHUN 2017 - Valeria Oktoviani; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study is entitled "Guiding the Village Head Against Posyandu in Baru Village, Siak Hulu District, Kampar Regency in 2017" This research is motivated by the inadequate guidance and implementation of the Posyandu in Baru Village, Siak Hulu Subdistrict, Kampar Regency, which based on Regent Regulation No. 6 of 2017 concerning Guidelines for Implementing Public Health Insurance and Kampar Law No. 15 of 2009, in which the Kampar District Government instructed health socialization and monitoring on a quarterly basis, but the implementation of the socialization and assistance had not yet been carried out. The formulation of the problem in this study is "How is the Development of Community Health Centers Against Posyandu in Baru Village, Siak Hulu District, Kampar Regency in 2017".          The method used in this study is a qualitative method that explains data descriptively. Data collection techniques used were interviews and documentation. While the data source used is primary data obtained from the research location in the form of research informants and subsequently supported by secondary data in the form of document data.The results of this study indicate that both the guidance and application of the implementation of posyandu have not been fully implemented either in the implementation of child birth and mortality reporting, procurement of posyandu facilities and infrastructure, socialization by posyandu cadres and distribution of vaccines and vitamins to posyandu in posyandu in Baru Village Siak Hulu District, Kampar Regency. Keywords: Development of Posyandu, Socialization of Vaccine and Vitamin Distribution